646 Appraisal of International Guidelines for Malignant Melanoma Management Using the AGREE II Assessment Tool. (4th May 2021) - Jacklin, C; Harrison, C; Tan, M; Sravanam, S
Abstract: Background: Recently, the widely accepted NICE guidelines for melanoma management have been challenged by a UK-based expert consensus statement. A review of alternative clinical practice guidelines (CPGs) could guide future CPG updates and developments. The AGREE II tool assesses CPGs across six domains: 'Scope and purpose', 'Stakeholder involvement', 'Rigour of development', 'Clarity of presentation', 'Applicability', and 'Editorial independence'. Method: We conducted a systematic search of Pubmed, Medline and online CPG databases to identify melanoma CPGs published between January 2014 and March 2020 providing recommendations for: adjuvant treatment, radiotherapy, surgical management, or follow-up care. Three authors independently assessed the quality of identified CPGs using the AGREE II assessment tool. Inter-rater reliability was assessed by Kendall's coefficient of concordance (W). Results: Twenty-nine CPGs were included and appraised with excellent reliability (Kendall's W for overall GPC score 0.85, p < 0.001). Overall, melanoma CPGs scored highly in the scope and purpose and clarity of presentation domains, and poorly in the applicability domain. The NICE guideline achieved the best overall scores. Conclusions: The NICE melanoma CPGs are higher quality than alternatives but should be updated to reflect recent landmark trials. The AGREE II tool is currently limited by its incapacity to compare guidelines to latest evidence.